The Inhibitory Effect of Aflatoxin on The Growht of Bacillus megaterium and Staphylococcus epidermidis - Eko Sugeng Pribadi; Unang Patriana; Titiek Sunartatie (Media Veteriner, 1998)
B. megaterium and S. epidermidis were used to study the inhibitory effect or pure aflatoxin and aflatoxin-contaminated rice. Results showed that the inhibitory effect was more pronounced In B. megatarium growth. The inhibitory effect of pure aflatoxin started at the concentration of 20 μg/ml and persisted to the concentration of 25 μg/ml (P